Persepsi Masyarakat Teluk Nibung Kota Tanjung Balai terhadap Istri sebagai Pencari Nafkah dalam Perspektif Hukum Islam - Dihati, Hasrat; Mukhsin, Abd. (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to examine the understanding of the people of Teluk Nibung, Tanjung Balai City, regarding the obligation of providing for the household according to Islamic law. The method used in this study is an empirical approach using interviews and observation. This study was also supported by documentation from the KUA (Office of Religious Affairs) and other religious institutions. The results of the study show that the understanding of the Teluk Nibung community regarding financial support is still limited to basic household needs such as food and shelter. People who have a deeper understanding of religion tend to understand financial support in a broader context, including education and health, and assume that the husband's obligation to provide financial support can be reduced or waived when the wife has an income. This study also reveals irregularities in the provision of nafkah, which are influenced by the family's economic conditions. The conclusion of this study is that the Teluk Nibung community's understanding of nafkah needs to be broadened through more comprehensive and continuous education regarding the obligation of nafkah in Islam.